Math, asked by kkritika792, 4 months ago

If ×=1/7,y=2/3and z= -1/3,verify that,x×(y+z)=(x×y)+(x×z).​

Attachments:

Answers

Answered by Anonymous
10

 \huge \purple{ \mid {\fbox{ \rm{solution}}}}

Given that x=1/7

y=2/3 and z=-1/3

we need to verify that (y+z)=(y)+(z)

so now we will put the values of

 \frac{1}{7}  \times  \frac{2 }{3}  +  \frac{ - 1}{3}  =  \frac{1}{7}  \times  \frac{2}{3}  +  \frac{1}{7}  \times  \frac{ - 1}{3}  \\  \frac{1}{21}  =  \frac{2}{21}  -  \frac{1}{21}  =  \frac{1}{21}

hence proved

hope it helps you ✌️

Similar questions